A Theoretical Review on EFL/ESL Teachers' Professional Development: Approaches, Applications, and Impacts - Li, Xiaodong (Frontiers in Psychology, 2022)
Teachers as the most important elements of education constantly need professional development (PD) courses in order to improve their pedagogy and practice. Given this, many educational systems worldwide have paid special attention to designing courses by which the quality of teaching and learning raises considerably. This surge of interest has ended in different studies on PD programs in L2 education. However, the pertinent literature lacks a comprehensive review of the models, applications, and impacts of EFL/ESL teachers’ PD and various aspects influenced by this construct. To fill this gap and add fresh insights into this strand of research, the present study aimed to review the definitions, characteristics, models, goals, and uses of TPD in L2 education. Moreover, several empirical studies were touched on to support the claims of TPD impact on teachers. Finally, the study presented different implications for L2 teachers, teacher trainers, researchers, and policy-makers who can realize the significance and impact of effective TPD courses on the whole process of teaching and learning.